Além da superfície : impactos do desenvolvimento da modernidade na pesca artesanal de Regência Augusta-ES - Bicalho, Charlene Sales (2012)
This study shows how the fishermen of Regency Augusta, district of Linhares-ES, ressignificam fishing and social practices in its work towards large-scale Projects (PGE’s) deployed both the rio Doce and maritime space. Want to be investigated from the loo